Automated alpha amino acid synthesis and selective removal of sensitizers from natural product extracts: Feverfew (Tanacetum parthenium) - Gajewski, Karol (University of Ottawa (Canada), 2004)
In an effort to synthesize alpha-amino acids via automated methods, the DKR reaction had to be adapted to work on a polymeric support. (R)-pantolactone was derivatized so that it could be incorporated into a polymer. The new derivative was also evaluated in some DKR reactions to make sure none of the efficacy was lost. The thesis describes the conversion of (R)-pantolactone into a number of N-aryl substituted gamma-lactams. Enantiomerically pure (R)-3-hydroxy-1-(4--methoxyphenyl)-4,4-dimethylpyrrolidin-2-one (19) was obtained via a seven step sequence in an overall yield of 27%. Racemic versions of several of these compounds (most notably the para methoxy 19 and unsubstituted 26) were produced in a one pot procedure. Compound 19 was acylated with several different alpha-bromo acids and evaluated as a chiral auxiliary in DKR reactions with a number of primary and secondary amines. The diastereomer ratios obtained were comparable or better than those observed in similar reactions when (R)-pantolactone was used as the auxiliary. The compound 26 was transformed via a series of reactions into 70 for polymerization using Grubbs ROMP approach. The polymer (75) obtained had molecular weights of 7000, 10,000 and 35,000 depending on the catalyst loading; with the latter showing a PDI of 1.09. These polymers were soluble in chloroform and thus easy to characterize by NMR. Removal of the TBDMS group afforded a highly insoluble polymer that proved difficult to acylate with alpha-bromoacids that were required to attempt the DKR reaction on a polymer supported chiral auxiliary. A modified version of the polymer 75 may be necessary to complete the original goal of this thesis.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Organic.